Transição agroecológica no sertão nordestino: um estudo de caso - Trajano, Janice Alves (2021)
A studying focus that has been growing and proving to be relevant in the field of Anthropology is interactions and associations between non-human beings, such as plants. Theme that gets new contours when we consider the challenges involved in ecologically based production inserted in an environment marked by uncertainties about water access, such as the hinterland of the Brazilian Northeast: sertão. In this way, the present research proposes to investigate how the relations between human beings and plant beings occur in a property in agroecological transition in the northeastern hinterland. For the purposo, a case study was carried out with a family living in the city of Exu, Pernambuco. Participant observation and unstructured interviews were part of the techniques to be used in the research. In this text, the plants will be presented in three forms. Initially, as a livelihood, by allowing the maintenance of life, living and the acquisition of goods and products. Then, plants are shown as food, covering the diversity and challenges involved in the exercise of food sovereignty. Finally, plants will be treated as a medicine, with emphasis on the issue of the transmission of traditional knowledge.